2016
DOI: 10.1080/13543784.2016.1201063
|View full text |Cite
|
Sign up to set email alerts
|

Investigational drugs in early development for treating dengue infection

Abstract: None of the handful of drugs tested so far has yielded encouraging results. Early trial experience has served to emphasize the challenge of drug testing in the short therapeutic time window available, the need for tools to predict 'high-risk' patients early on and the limitations of the existing pre-clinical model systems. Significant investment of efforts and resources is a must before the availability of a safe, effective and inexpensive dengue drug becomes a reality. Currently, supportive fluid therapy rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…Thus, a drug for treating dengue illness is an unmet public health need. Current dengue drug discovery efforts are based either on high throughput screening of compound libraries for potential antiviral inhibitors or re-purposing of existing clinical compounds which have been developed previously for other disease indications [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a drug for treating dengue illness is an unmet public health need. Current dengue drug discovery efforts are based either on high throughput screening of compound libraries for potential antiviral inhibitors or re-purposing of existing clinical compounds which have been developed previously for other disease indications [15].…”
Section: Discussionmentioning
confidence: 99%
“…Introduction drug development [15]. Thus, celgosivir, a drug initially intended for treating HCV infection, was tested for antiviral efficacy against dengue.…”
Section: Original Article a Quinoline Compound Inhibits The Replication Of Dengue Virus Serotypes 1-4 In Vero Cellsmentioning
confidence: 99%
“…Corticosteroid is mainly adopted as an adjunct immunomodulatory treatment for diseases caused by immune responses [48]. Immune pathology of dengue has similarities to other autoimmune diseases that have been successfully treated by corticosteroids [48,62]. A clinical trial has shown the supportive evidence for the actions of methylprednisolone to prevent dengue progression to DHF or DSS [63].…”
Section: Drug Repurposing For Dengue Therapymentioning
confidence: 99%
“…Though several attempts have been made for development of drugs against dengue, the efforts have not yielded a safe and effective drug so far. [16][17][18]. Several drugs such as chloroquine [19], celgosivir [20], lovastatin [21], balapiravir [22], prednisolone [23] have been evaluated for their ability to treat dengue infection and disease.…”
Section: Introductionmentioning
confidence: 99%